SAFETY, SOCIAL RELATIONS AND SATISFACTION IN POSTDISASTER RESETTLED COMMUNITIES: A CASE OF KEDAH, MALAYSIA - Isa, Mohd Ismail; Marzbali, Massoomeh Hedayati; Azizan, Izzati Hilda (PLANNING MALAYSIA, 2021)
This research aims to study the changes in physical and social patterns among tsunami victims in Kedah, Malaysia by examining the relationship between their perceptions of safety and satisfaction. Data were obtained through a questionnaire survey on 109 respondents who live in Taman Permatang Katong, a new housing area built by the federal government. Results indicated the positive relationship between perception of safety and satisfaction. Meanwhile, social relations played a mediating role on the relationship between perception of safety and satisfaction. This finding implies that those who perceived the new resettlement area to be safer reported higher levels of social relations and, consequently, higher levels of satisfaction. Overall, the majority of residents in Taman Permatang Katong are satisfied with their new houses after the tsunami and feel safe in their area of residency. In conclusion, the resettlement programme should be well planned and should consider both social and physical aspects to improve the well-being of residents.